THE WAYS OF REPRESENTATION OF NONVERBAL ELEMENTS OF BUSINESS DISCOURSE IN TRANSLATION - Anvarbekova Shoira Anvarbek qizi (Journals Park Publishing, 2023)
Language is the universal and primary mode of communication between people; however, information is transmitted not only with the help of verbal component, but also with the help of non-verbal signals. Communication is among the most frequently used ones in a number of branches of our modern globalized world. It has been very much preferred in business, where it can lead to great success accompanied with large profits or be blamed for failure and large losses. However, communication is far from being just about words or letters. Quite frequently communication is also about success in business, politics, art or good interpersonal relations. The paper is an attempt to give some more details on how gestures important in business discourse and present ways of translating non-verbal elements.
Keywords: communication, non-verbal elements, business discourse, translation.